Carry-over effects of resource competition and social environment on aggression. (12th October 2019) - Kilgour, R J; Norris, D R; McAdam, A G
Abstract: Aggressive behavior is common in many species and is often adaptive because it enables individuals to gain access to limited resources. However, aggression is also highly plastic and the degree of plasticity could be influenced by factors such as resource limitation and the social environment. In this study, we examined how the effects of social experience and resource limitation could persist to affect future aggressive interactions. Using naturally inbred strains of Drosophila melanogaster that differ in aggressiveness, we manipulated the level of available resources by varying fly density (two treatments: high and low per capita resources) and group composition by varying strain frequency (five treatments: homogeneous strains, or mixed at 1:3, 1:1 or 3:1 ratios of the more aggressive to less-aggressive strain). For each treatment group, we measured aggression before and after flies were placed through a 4-day period of fixed resources. There was no consistent effect of resource competition on aggression. Instead, changes in aggression depended on resource availability in combination with group composition. In homogeneous groups made up of only one strain, all males became more aggressive following the fixed-resource period, regardless of fly density. In mixed-strain treatments at high density, we observed plastic shifts in aggression of males from both strains, but the direction of plastic responses depended on social composition. Our results show that aggression may not only be influenced by the intensity of previous competitive experiences caused by resource limitation, but also through social effects caused by the composition of the group. Lay Summary: An animal's expression of aggression can change over time, partly due to previous experiences with other individuals, and can persist across time and space. We created environments where fruit flies competed for food, competitors were either aggressive or non-aggressive, and they were mixed at different ratios. We tested subsequent changes in aggression as a result of these competitions. Male aggression was affected by their competitive experience, but the impact depended on the group makeup during competition.